Rāmāyaṇa : mahātmya, kshepaka, aura Śrīraghunāthadāsajīkrta Viśrāmaaṅga, Tulasīdāsajīkrta Vinayapatrikā, aura unakā jīvanacaritra, Rāmajanma tithipatra, Rāmakalevā, Baravā Rāmāyaṇa, Hanumānacālīsā, Saṅkaṭamocana, prasaṅgānusāra itihāsa ślokārtha, stutyartha, chandārtha, guḍhārthadīpikā, ṭipaṇṇī, pāṭhāntara, bahirlāpikā, citrabandha, mantrātmaka, Māruticitra, aura Ashṭamalavakuśakāṇḍasahita - Tulasīdāsa, 1532-1623 (Gauḍabrāhmaṇa Hariprasāda Bhagīrathajī, 1923)
Verse work on Rāma, Hindu deity.